A novel α‑l‑rhamnosidase with potential applications in citrus juice industry and in winemaking - Alvarenga, Adriana Elizabet (2013)
The production of monoglycosylated flavonoids by α-l-rhamnosidases (EC 3.2.1.40) is an interesting development in biocatalysis. Applications of rhamnosidases in industry include removal of bitterness caused by naringin from citrus juices. In the present work, a psychrotolerant bacterial strain with α-l-rhamnosidase activity was isolated. The α-l-rhamnosidase was found to be able to degrade naringin and was purified and characterized. The α-l-rhamnosidase from Brevundimonas sp. Ci19 was able to release both rhamnose and prunin from naringin. The enzyme was partially purified with a performance of 2.7-fold purification. The α-l-rhamnosidase showed an optimum pH between 6.00 and 7.00 with substantial residual activity at pH 5.00 (85.3 %). The optimum temperature was between 20 and 37 °C. The enzyme showed activation in the presence of Ca2+ and Cd2+ ions and at a high ethanol concentration level (10 % v/v). Activity was found for β-d-glucosidase (EC 3.2.1.21) in the partially purified extract, but it was inactive in the acid pH region. This result indicates the potential for inactivation of β-d-glucosidase along with the high level of α-l-rhamnosidase activity necessary for the production of flavonoid glycosides. The α-l-rhamnosidase from Brevundimonas sp. Ci19 showed interesting properties for potential use not only in the citrus juice industry but also in winemaking.